The Question of The Coherence of Phraseological Units with The Frequency of Speech - Musaev A.S.; Maxatova D. (Zien Journals, 2021)
The article deals with a partial-of-speech classification of phraseological units of modern Russian. In particular, the controversial questions of the part of speech belonging to phraseological units.
Keywords: Phraseology; parts of speech; species correlation; free and related word combinations